Fighting Inequality: Progress Made Under G20 Brazil and the Priorities for South Africa - David Francis (My University, 2024)
In the latter half of the 20th century, notable progress was made globally in addressing poverty and hunger, with significant reductions in poverty in large parts of the world. However, alongside these achievements came a rapid growth in inequalities of income and wealth within countries, alongside the persistence of inequalities in race and gender, among others.
In the latter half of the 20th century, notable progress was made globally in addressing poverty and hunger, with significant reductions in poverty in large parts of the world. However, alongside these achievements came a rapid growth in inequalities of income and wealth within countries, alongside the persistence of inequalities in race and gender, among others.
Keywords: SDG-10: Reduced inequalities